A 6-month prospective study of injury in Gaelic football. Issue 5 (30th November 2006) - Wilson, F; Caffrey, S; King, E; Casey, K; Gissane, C
Abstract : Objective: To describe the injury incidence in Gaelic football. Methods: A total of 83 players from three counties were interviewed monthly about their injury experience, during the 6 months of the playing season. Results: The injury rate was 13.5/1000 h exposure to Gaelic football (95% CI, 10.9 to 16.6). There were nearly twice as many injuries during matches (64.4%, 95% CI, 54.1 to 73.6) as in training (35.6%, 95% CI, 26.4 to 49.5). The ankle was found to be the most commonly injured site (13.3%, 95% CI, 7.8 to 21.9). The musculotendinous unit accounted for nearly 1/3 of all injuries (31.1%). The tackle accounted for 27.8% of the injuries sustained (tackler 10%, 95% CI, 5.4 to 17.9; player being tackled 17.9%, 95% CI, 11.2 to 26.9). Of total match injuries, 56.9% (95% CI, 46.1 to 67.1) were experienced in the second half as opposed to 39.7% (95% CI, 29.8 to 50.5) in the first half. Conclusions: Gaelic footballers are under considerable risk of injury. Greater efforts must be made to reduce this risk so that players miss less time from sport due to injury. Risk factors for injury in Gaelic football must now be investigated so that specific interventions may be established to reduce them.